THE EFFECT OF USING PQ4R METHOD ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMK PESANTREN DAREL HIKMAH PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Suci Rahmini; Syofia Delfi; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was designed to experiment the effect of using PQ4R method on the ability of the first year students of SMK Pesantren Darel Hikmah Pekanbaru in comprehending recount texts. The aim was to find out the effect of using PQ4R method on the ability of the first year students of SMK Pesantren Darel Hikmah Pekanbaru in comprehending recount texts. This research took place in SMK Pesantren Darel Hikmah Pekanbaru, that collected from April to May 2018. The try out class was X TI class (17 students) and the sample was X Perbankan Syari’ah (25 students) chosen by cluster random sampling. This is a pre-experimental research with one group pre-test, post-test design. This research used quantitative data and the instrument used to collect the data was a reading test in multiple choice forms. As the result, the mean score of pre-test is 48.28 and the mean score of post-test is 56.20. In other words, the mean score of post-test is higher than the mean score of pre-test. The result also showed that the value of t-test (2.283) is higher than t-table (2.064) at the significance level 5%. It means that Alternative Hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. It means that, there is any effect of using PQ4R method on the ability of the first year students of SMK Pesantren Darel Hikmah Pekanbaru in comprehending recount texts. It is suggested that in understanding recount text is one of alternative , the teacher needs to focus on the students’ understanding the sentences on the texts.Keywords: Comprehension, PQ4R Method, Recount Text.